Building the data warehouse - Inmon, William H. (Wiley Pub., 2005)
"Data warehouses provide a much-needed strategy for organizations to collect, store, and analyze vast amounts of business data. As businesses expand both brick-and-mortar and online activities, the field of data warehousing has become increasingly important. Since it was first published in 1990, W.H. Inmon's Building the Data Warehouse has been the bible of data warehousing - it is the book that launched the data warehousing industry and it remains the preeminent introduction to the subject. This new edition covers the latest developments with this technology, many of which have been pioneered by Inmon himself."--Jacket.